Magnetic Properties of Exchange-Biased [Co/Pt](n) Multilayer With Perpendicular Magnetic Anisotropy - COEY, JOHN; FENG, JIA-FENG; DIAO, ZHU (My University, 2010)
Perpendicular exchange-biased [Co/Pt](3)/Co(t(Co))/IrMn and IrMn/Co(t(Co))/Pt/[Co/Pt](3) multilayers have been fabricated, changing the thickness (t(Co)) of the cobalt that is next to the IrMn layer. The crystal structure, interface roughness and magnetic properties were characterized by X-ray diffraction (XRD), X-ray reflectivity (XRR), atomic force microscopy (AFM) and extraordinary Hall Effect (EHE). The multilayers are flat, and the roughness is about 0.2 nm across the 2-mu m scanning range. The magnetization reversal is dependent on t(Co), and the exchange bias and coercivity vary with t(Co). The exchange bias reaches a maximum value (about 13.9 mT) for top-pinned multilayers at t(Co) = 0.45 nm, while it reaches a maximum (about 3.5 mT) for bottom-pinned multilayers at t(Co) = 0.6 nm. For both stacks the coercivity is maximum (about 30 mT) at t(Co) = 0.8 nm, and stable for t(Co) > 1.0 nm. These results are well understood in terms of the Co spin orientation at the Co/ IrMn interface.
PUBLISHED
Keywords: MAGNETICS; INTERFACE ROUGHNESS; Nanoscience & Materials